2006
DOI: 10.1038/sj.bjc.6602993
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of mitochondrial D-Loop mutations in head and neck carcinoma

Abstract: Mitochondrial DNA mutations have been reported in several types of tumours, including head and neck squamous cell carcinoma (HNSCC). The noncoding region of the Displacement-Loop (D-Loop) has emerged as a mutational hotspot and we recently found that they were associated with prognosis and response to 5 fluorouracil (5FU) in colon cancers. In order to evaluate the frequence of D-Loop mutations in a large series of HNSCC and establish correlations with clinicopathologic parameters, we sequenced the D-Loop of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
2
47
0
1
Order By: Relevance
“…In addition to quantitative change of mtDNA copy number, several studies also evaluated the qualitative mtDNA D310 mutations in human types of cancers, including prostate (50,51), head and neck (52) and lung cancer (53,54), and esophageal squamous cell carcinoma (20), and some showed clinical significance. In breast cancer, a D-loop mutation, including D310 mutation, was identified as a poor prognostic factor (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to quantitative change of mtDNA copy number, several studies also evaluated the qualitative mtDNA D310 mutations in human types of cancers, including prostate (50,51), head and neck (52) and lung cancer (53,54), and esophageal squamous cell carcinoma (20), and some showed clinical significance. In breast cancer, a D-loop mutation, including D310 mutation, was identified as a poor prognostic factor (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mutations in the D-loop sequence were also conducted by Lièvre et al (21). Their analyses involved patients with head and neck tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore it is shown that the mutations previously reported within the ND2 gene in normal parotid tissue of smokers were not evident in these samples, but that a mutation hotspot occurs at nucleotide 4917 in oral SCC.It is concluded that the mtDNAmutations hotspot found in this study in particular nt186 are potential biomarkers for oral SCC. 20,26,27 D-loop mutations should be considered as a cancer biomarker that may be useful for the early detection of HNSCC in individuals at risk of this cancer. The presence of these mutations in saliva and serum of tobacco and alcohol consumers' should be investigated in further studies in order to evaluate their relevance in the screening of these cancers in association with other tumour specific molecular alterations.…”
Section: Role Of Tumour Suppressor Gene Sdh Mutation In Tumour Formationmentioning
confidence: 99%
“…The presence of these mutations in saliva and serum of tobacco and alcohol consumers' should be investigated in further studies in order to evaluate their relevance in the screening of these cancers in association with other tumour specific molecular alterations. 21,26 MtDNA as a marker in histopathologic grading in premalignant and malignant head and neck lesions Mitochondria are highly susceptible to oxidative damage and mitochondrial function decreases with oxidative damage, overall mitochondrial DNA content increases to compensate for general mitochondrial dysfunction. 9 Head and neck squamous cell carcinomas arise through premalignant intermediates and may be merely morphologic manifestations of accumulated genetic alterations.…”
Section: Role Of Tumour Suppressor Gene Sdh Mutation In Tumour Formationmentioning
confidence: 99%